A Critical Evaluation of Three Sesotho Dictionaries - Setaka, Mmasibidi; Prinsloo, D.J. (Lexikos, 2020)
This article gives a perspective on Sesotho lexicography and a critical analysis of the macrostructures and microstructures of three selected Sesotho dictionaries. The monolingual paper dictionary SethantÅ¡o sa Sesotho, the bilingual paper dictionary Southern Sotho–English Dictionary and the Sesotho online Bukantswe v.3 are evaluated. Their virtues and shortcomings as reference works will be viewed against dictionaries of high lexicographic achievement in order to establish to what extent they fulfil the most basic requirements of macrostructures and microstructures. The inconsistencies addressed in this article reflect the need for Sesotho lexicographers to use corpora in dictionary compilation in order to enhance the quality of entries on both microstructural and macrostructural levels. It will be argued that much more research and description of lexicographic issues is required to bring Sesotho lexicography on a par with its sister languages, Sepedi and Setswana and with good dictionaries for major languages of the world. After decades in existence, currently available Sesotho dictionaries are in dire need for revision and new dictionaries aimed at specific target users should be compiled.